The Influence of Organizational Culture and Leadership on Performance Organization through the Implementation of National Standards for Childcare As an Instrument of LKSA Accreditation At Children's Social Welfare Institutions Karawang Regency - Mohamad Taufik; Imam Wibowo; Guswandi (Journal of Islamic Studies & Social Science, 2024)
This study aims to: 1) determine and analyze the effect of organizational culture and leadership and on the implementation of national childcare standards as an accreditation instrument, 2) determine and analyze the effect of organizational culture and leadership on organizational performance, 3) determine and analyze the effect of implementing national childcare standards on organizational performance, 4) determine and analyze the effect of organizational culture and leadership on organizational performance through the implementation of national childcare standards as an accreditation instrument. The research was conducted at the Karawang Regency Child Social Welfare Institution, the research sample was 53 respondents. The sampling technique used saturated sampling technique. The data analysis method uses descriptive analysis and path analysis. The results showed that: 1) there is an influence of organizational culture and leadership and on the implementation of national childcare standards as an accreditation instrument, 2) there is an influence of organizational culture and leadership on organizational performance, 3) there is an influence of the implementation of national childcare standards on organizational performance, 4) there is an influence of organizational culture and leadership on organizational performance through the implementation of national childcare standards as an accreditation instrument. The variable application of national childcare standards as an accreditation instrument does not play a role in organizational culture and leadership and organizational performance.